Late 18th – mid 20th centuries manor houses in Ukraine - Yakubovskyy, Ihor (Видавництво Львівської політехніки, 2013)
The paper analyzes the main directions of Ukrainian manor house development as well as defines the place of manor housing in Lviv on the Ukrainian historical background. The approaches to urban manor houses preservation are proposed.
Keywords: manor house; housing; Lviv; detached house; palace; cottage; urban architecture